2008
DOI: 10.1016/j.jmb.2008.03.026
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Mode of Microtubule Stabilization Induced by Peloruside A

Abstract: Microtubules are significant therapeutic targets for the treatment of cancer, where suppression of microtubule dynamicity by drugs such as paclitaxel forms the basis of clinical efficacy. Peloruside A, a macrolide isolated from New Zealand marine sponge Mycale hentscheli, is a microtubule-stabilizing agent that synergizes with taxoid drugs through a unique site and is an attractive lead compound in the development of combination therapies. We report here unique allosteric properties of microtubule stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
151
3
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(171 citation statements)
references
References 50 publications
16
151
3
1
Order By: Relevance
“…This difference appears to be related to the binding modes of the drugs in CET, which are also characterized in the present study, and is, therefore, consistent with the previously observed synergistic activities of different MSA combinations (19 -22). Furthermore, we find a significant deviation between the binding modes and the stabilizing activities of MSAs in CET as compared with those reported in BBT (16). As the major difference between the two sources of tubulin is the isotype composition, our results emphasize the importance of tubulin isotype content on drug binding and MT stabilization.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…This difference appears to be related to the binding modes of the drugs in CET, which are also characterized in the present study, and is, therefore, consistent with the previously observed synergistic activities of different MSA combinations (19 -22). Furthermore, we find a significant deviation between the binding modes and the stabilizing activities of MSAs in CET as compared with those reported in BBT (16). As the major difference between the two sources of tubulin is the isotype composition, our results emphasize the importance of tubulin isotype content on drug binding and MT stabilization.…”
supporting
confidence: 46%
“…Several possibilities have been proposed for where this alternative site may be. Although computational studies based on NMR suggested that the most likely binding site for laulimalide and peloruside A is in ␣-tubulin (23), hydrogen-deuterium exchange mass spectrometry (HDX-MS) experiments similar to those utilized in the current study proposed a binding site adjacent to the taxane pocket in the ␤-tubulin subunit (16). The latter work also proposed a distinct mode for MT stabilization for peloruside A, with relaxation of intradimer contacts and ␤-␤ interactions across the lateral interface accompanying binding.…”
mentioning
confidence: 83%
“…The binding sites 1 and 2 are located in b-tubulin, while binding site 3 is in a-tubulin. The binding site 1 consists of b-tubulin residues Gln291, Ala296, Lys336 and Asn337, and it is basically in agreement with the alternative site previously reported 13,14 . The binding site 2 is made up of b-tubulin residues Asp224, His227, Thr274, Arg276, Arg282 and Gly360, and it just located in the well-known taxane site.…”
Section: Molecular Dockingsupporting
confidence: 89%
“…In docking mode 1, the binding site is composed of b-tubulin residues Pro287, Thr290, Gln291, Gln292, Phe294, Asp295, Ala296, Pro305, Arg306, Gln329, Asn332, Val333, Lys336, Asn337 and Tyr340. It is worth the whistle, the previous experimental study has reported that the candidate region for PLA-binding site, being called the alternative site 14 , is composed of peptides b294-301 (H9-H9 0 loop), b302-314 (H9 0 -S8) and b332-340 (H10 loop) detected by HDX-MS 13 . It is easy to find that the most key residues (Phe294, Asp295, Ala296, Pro305, Arg306, Asn332, Val333, Lys336, Asn337 and Tyr340) of the binding site 1 predicted by the docking appear in the alternative site.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation